Corrosion study of hydrothermally deposited coatings on AZ31 Mg alloys - Zool Ikhsan Abdul Rahman (2014)
Magnesium is the lightest of all structural engineering metals used today, 33% lighter than aluminium and 75% lighter than steel. It has good ductility, electromagnetic interference reduction, excellent castability and, through proper alloying, also high strength. Although it is often used in lightweight construction, wider applications of magnesium are still limited due its poor corrosion resistance. As a proposed solution, conversion coatings for AZ31 Mg alloys using hydrothermal deposition were developed in this study. Magnesium phosphate coatings deposited at 130°C for 3 hours using 0.06M NH4H2PO4 solution resulted in a closely packed crystal-like surface morphology. The obtained corrosion potential (-0.613V) was more positive than the untreated substrate (-1.449V). The corrosion current density (1.22x10-7Acm-2) was also reduced by three orders of magnitude (1.11x10-4Acm-2). Under salt spray conditions, the magnesium phosphate coating experienced severe pitting corrosion after 8 days. The sample was then completely covered with magnesium hydroxide corrosion by-products after 25 days. Zinc phosphate coatings deposited at 160°C for 3 hours using 0.06M NH4H2PO4 + 0.10M Zn3(PO4)2 solution also resulted in a crystal-like surface coating and improved corrosion resistance (Ecorr = -0.724V, Icorr = 2.12x10-4Acm-2). Building on present research, this study showed that the hydrothermal deposition method could be expanded further to produce corrosion resistant magnesium phosphate and zinc phosphate coatings. This method is low cost, simple and allows for the application of an even surface coating regardless of the specimen shape or form. Thus it provides a useful alternative to produce small corrosion resistant parts for use in wider engineering applications.